Global, Regional, and National Burden of Diabetes-Related Chronic Kidney Disease From 1990 to 2019 - Deng, Yujiao; Li, Na; Wu, Ying; Wang, Meng; Yang, Si; Zheng, Yi; Deng, Xinyue; Xiang, Dong; Zhu, Yuyao; Xu, Peng; Zhai, Zhen; Zhang, Dai; et al. (Frontiers in Endocrinology, 2021)
Background Chronic kidney disease (CKD) is a public health problem largely caused by diabetes. The epidemiology of diabetes mellitus related CKD (CKD-DM) could provide specific support to lessen global, regional, and national CKD burden. Methods Data was derived from the GBD 2019 study, including four measures and age-standardized rates (ASRs). Estimated annual percentage changes and 95% CIs were calculated to evaluate the variation trend of ASRs. Results Diabetes caused the majority of new cases and patients with CKD in all regions. All ASRs for type 2 diabetes related CKD increased over 30 years. Asia and Middle socio-demographic index (SDI) quintile always carried the heaviest burden of CKD-DM. Diabetes type 2 became the second leading cause of CKD and CKD related death, and the third leading cause of CKD related DALYs in 2019. Type 2 diabetes related CKD accounted for most of the CKD-DM disease burden. There were 2.62 million incident cases, 134.58 million patients, 405.99 thousand deaths and 13.09 million disability-adjusted life-years (DALYs) of CKD-DM worldwide in 2019. Age-standardized incidence (ASIR) and prevalence rate (ASPR) of type 1 diabetes related CKD increased, whereas age-standardized death rate (ASDR) and DALY rate decreased for females and increased for males. In high SDI quintile, ASIR and ASPR of type 1 diabetes related CKD remained the highest, with the slowest increase, whereas the ASDR and age-standardized DALY rate remained the lowest. In high SDI quintile, ASIR of type 2 diabetes related CKD was the highest, with the lowest increasing rate. In addition, type 2 diabetes related CKD occurred most in people aged 80 plus years worldwide. The main age of type 2 diabetes related CKD patients was 55-64 years in Asia and Africa. The prevalence, mortality and DALYs rate of type 2 diabetes related CKD increased with age. As for incidence, there was a peak at 80 years, and after age of 80, the incidence declined. CKD-DM related anemia was mainly in mild to moderate grade. Conclusions Increasing burden of CKD-DM varied among regions and countries. Prevention and treatment measures should be strengthened according to CKD-DM epidemiology, especially in middle SDI quintile and Asia.